Monitoring persistent organic chemicals in Antarctica in support of global chemical policy: a horizon scan of priority actions and challenges - Bengtson Nash, Susan; Bohlin-Nizzetto, Pernilla; Galban-Malagon, Cristobal; Corsolini, Simonetta; Cincinelli, Alessandra; Lohmann, Rainer (The Lancet Planetary Health, 2023)
Summary Global production and emission of chemicals exceeds societal capacities for assessment and monitoring. This situation calls for improved chemical regulatory policy frameworks and increased support for expedited decision making within existing frameworks. The polar regions of the Earth represent unique sentinel areas for the study of global chemical behaviour, and data arising from these areas can strengthen existing policy frameworks. However, chemical pollution research and monitoring in the Antarctic is underdeveloped, with geopolitical complexities and the absence of legal recognition of international chemical policy serving to neutralise progress made in other global regions. This Personal View represents a horizon scan by the action group Input Pathways of Persistent Organic Pollutants to Antarctica, of the Scientific Committee for Antarctic Research. Four priority research and research facilitation gaps are outlined, with recommendations for Antarctica Treaty parties for strategic action against these priorities.
Keywords: Antarktis; Sørishavet; forskning; forvaltning; helse; miljøgifter

Microplastic in the surface waters of the Ross Sea (Antarctica): Occurrence, distribution and characterization by FTIR - Cincinelli, Alessandra; Scopetani, Costanza; Chelazzi, David; Lombardini, Emilia; Martellini, Tania; Katsoyiannis, Athanasios; Fossi, Maria Cristina; Corsolini, Simonetta (Chemosphere, 2017)
This is the first survey to investigate the occurrence and extent of microplastic (MPs) contamination in sub surface waters collected near-shore and off-shore the coastal area of the Ross Sea (Antarctica). Moreover, a non-invasive method to analyze MPs, consisting in filtration after water sampling and analysis of the dried filter through Fourier Transform Infrared Spectroscopy (FTIR) 2D Imaging, using an FPA detector, was proposed. The non-invasiveness of analytical set-up reduces potential bias and allows subsequent analysis of the filter sample for determination of other classes of contaminants. MPs ranged from 0.0032 to 1.18 particle per m3 of seawater, with a mean value of 0.17 ± 0.34 particle m−3, showing concentrations lower than those found in the oceans worldwide. MPs included fragments (mean 71.9 ± 21.6%), fibers (mean 12.7 ± 14.3%), and others (mean 15.4 ± 12.8%). The presence of different types of MPs was confirmed by FTIR spectroscopy, with predominant abundance of polyethylene and polypropylene. The potential environmental impact arising from scientific activities, such as marine activities for scientific purposes, and from the sewage treatment plant, was also evidenced.
Keywords: Rosshavet; Sørishavet; forurensning; mikroplast; miljøgifter